Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

Sous le développement, le genre - Verschuur, Christine; Guérin, Isabelle; Guetat-Bernard, Hélène (IRD Éditions, Institut de Recherche pour le Développement, 2015)
Du site de l'éd. : Ignorée, invisible, la question du genre reste cachée sous le développement. Et pourtant, comprendre le développement n'est pas possible sans une perspective de genre. Cet ouvrage, didactique, montre en quoi et comment le concept de genre permet de revisiter les études de développement. Le genre permet de comprendre la construction historique, sociale et culturelle des diffé- rences et des inégalités. Il offre des outils pour une analyse critique du système capitaliste globalisé. Le genre, inscrit dans le féminisme, permet aux catégories dominées et marginalisées, en particulier les femmes mais pas seulement, de faire entendre leurs voix. Dans le contexte actuel de crise globale et d'accroissement des inégalités, il propose des pistes pour renouveler la pensée sur le développement, mais aussi pour agir autrement. Combinant diverses disciplines et thématiques, cet ouvrage montre que la portée heuristique du genre ne se limite pas aux domaines habituellement considérés comme féminins (l'éducation, la famille, le social, la santé de la reproduction, etc.) mais s'étend à tous les domaines (le politique, le droit, la sécurité, la diplomatie, l'économie, etc.).Ce livre met aussi en évidence la diversité et l'enrichissement mutuel des diverses traditions de recherche entre le monde francophone, anglophone et hispano- phone. Il s'adresse particulièrement aux personnes étudiantes, chercheures et enseignantes, militantes, chargées de programme dans des organisations de coopération et représentantes des pouvoirs publics au Nord et au Sud.
Le chapitre “Une histoire du développement au prisme du genre. Perspectives féministes et décoloniales” de Verschuur, Christine, et al. 2015, pp. 43-71. a été donné en lecture dans le cours POL4022
Keywords: agriculture; anthropologie; approches et analyses; corps; cours; discipline; droit; environnement; féminisme décolonial; féminisme matérialiste; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; relations internationales; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sciences humaines; sociologie; thématiques; travail; économie